Role of cholinergic innervation in biliary remnants of patients with biliary atresia - Yang, Jixin; Chen, Xiaoqing; Wang, Wenjing; Su, Yanwei; Liu, Keqin; Abudusalamu, Adila; Li, Dandan; He, Ying; Wang, Pusu; Xiong, Xiaofeng; Feng, Jiexiong (Frontiers in Pediatrics, 2024)
Objective: Biliary innervation is considered to be important in regulating functions of bile ducts, whereas the roles of innervation in hepatobiliary system of patients with biliary atresia (BA) remain unknown. This current study aims to investigate the characteristics of innervation in biliary remnants, and to analyze the relationship between the innervation and prognosis of BA after surgery. Methods: Eighty-seven patients with type Ⅲ BA who underwent Kasai procedure were consecutively recorded from January 2017 to September 2020. Innervation and ductules in remnants were examined by pathologists. Liver function, onset of cholangitis, jaundice clearance and survival with native liver were recorded. Patients were followed up for 24 months. Relationship between innervation and prognosis were analyzed. Results: Totally, 67 patients had bile drainage postoperatively, and 21 biliary remnants contained neuronal plexuses where there was no neuron but nerve fiber bundles. Acetylcholinesterase staining was positive in all plexuses. In patients with bile drainage, those with plexuses had improved postoperative liver function, significantly better jaundice clearance 3 or 6 months postoperatively (50.0% vs. 19.1%, and 90.0% vs. 63.8%), fewer episodes of early cholangitis (10.0% vs. 34.0%) and better survival (80.0% vs. 61.7%) compared to those without. Additionally, larger area of plexuses was associated with larger area of ductules (R2=0.786, p=0.000), less frequent (p=0.000) and later cholangitis onset (p=0.012) and better jaundice clearance (p=0.063). Conclusions: Increased cholinergic innervation in biliary remnants may help reduce onset of cholangitis and lead to better and earlier jaundice clearance. Thus, it improves postoperative prognosis of patients with BA.